Developing a competency assessment framework for pharmacists in primary health care settings in India - Sanjeev Kumar; Purnima Bhoi; Manjiri Sandeep Gharat; Guru Prasad Mohanta (PLoS ONE, 2025)
Background Competency frameworks in the pharmacy profession define the necessary practice standards and establish benchmarks for work accountability and career progression. Pharmacists are integral to primary healthcare, and assessing their competencies is essential for improving the performance of primary healthcare services. Although several countries have developed competency frameworks for pharmacists in primary healthcare, such frameworks are currently lacking in India. Methods This study aimed to develop a competency assessment framework for in-service pharmacists in Indian public primary healthcare settings. For which, a five-stage consultative process was followed. In the first stage, the systematic literature review was conducted to identify pharmacist competencies in the primary healthcare setting. After that, an expert consultation was organized to develop consensus among experts on competencies and its behaviours. Competency assessment tools were then developed based on the literature and later finalized through experts’ agreements during consultation. Finally, the tools were tested in one of the public primary healthcare facilities. Results In stage one, the systematic literature review identified 20 competencies and 175 associated behaviors distributed across four domains: Pharmaceutical Health, Pharmaceutical Care, Organization and Management, and Professional/Personal. Expert consultations resulted in the consensus on 11 roles as domains of pharmacists in Indian primary healthcare settings during stage 2. During the expert consultation, each one of 11 pharmacist’s role and competencies and behaviours was discussed and consensus was arrived on 26 competencies and 107 behaviours. For which, under the role of pharmacy management, one of the critical competency for primary health care pharmacist is the knowledge about the layout and infrastructure of the pharmacy/store and how to adapt it to optimize pharmacy services. For this competency, one of the behaviour is assessment of the existing infrastructure and identifying gaps and opportunities for improvement. After that in stage 3, a competency assessment tool was developed, and consensus was made on it in stage 4 during expert consultation. The developed tool contains instruments such as a questionnaire to assess knowledge and attitude, and observational checklist, mini-clinical exercises for specific conditions, and simulation exercises to assess skills. Conclusions This study successfully developed a competency assessment framework for in-service pharmacists in Indian public primary healthcare settings. The framework encompasses 24 competencies and associated behaviors, covering 11 roles of pharmacists in Indian primary healthcare settings. For example, under the pharmacy management role, some of the competencies include planning and procurement, inventory management, storage conditions, digital literacy to handle supply chain-led IT Systems, NSQ Medical Products Management, etc. The developed competency assessment tool assessing knowledge, attitude and skills provides a comprehensive framework for assessing pharmacist competencies and identifying competency gaps. The framework can be used to capacitate pharmacists and improve their performance. It improves their performance in primary healthcare settings, and enhance the delivery of healthcare services in India. Additionally, it fills a critical gap in the existing literature and can serve as a valuable resource for policymakers, educators, and healthcare professionals involved in pharmacy practice in primary care settings.